TRANSFORMASI MANAJEMEN KOMUNIKASI PESANTREN : MENJAGA ETIKA DAN EFEKTIVITAS KOMUNIKASI SANTRI - Rofiatun Nisa'; Muhammad Ainul Yaqin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Islamic boarding schools (pesantren) are Islamic educational institutions with a structured system of life with a strong emphasis on fostering morals, discipline, and responsibility among students. With the advancement of communication technology, Islamic boarding schools face new challenges in managing student communication with external parties, particularly parents. One emerging form of communication is interlocal communication, a long-distance communication that allows students to stay connected with their families even within the Islamic boarding school environment. This study aims to analyze the transformation of interlocal communication management at the Nurul Jadid Islamic Boarding School in the Al-Mawaddah Region and its role in maintaining effective communication, time discipline, and the implementation of ethical values ​​among students.This research used a descriptive qualitative approach with a case study design. Data collection techniques included in-depth interviews, field observations, and documentation. The research informants consisted of junior high and senior high school students, interlocal officers, and the regional head. Data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The research results show that the long-distance communication management system has undergone a significant transformation from a simple system to a more structured and controlled one. This transformation is marked by the implementation of Standard Operating Procedures (SOPs), communication scheduling, duration restrictions, administrative record-keeping, and an increased role for staff in mentoring and supervision. This system has been proven to help students manage their time in a disciplined manner so that communication does not interfere with the primary obligations of the Islamic boarding school. Furthermore, the Islamic boarding school consistently instills ethical values ​​of Islamic communication, such as politeness, honesty, responsibility, patience, and self-control. Thus, long-distance communication management functions not only as a technical means of communication but also as a medium for developing the students' character integrated with Islamic educational values.